2021
DOI: 10.1186/s13643-021-01731-4
|View full text |Cite
|
Sign up to set email alerts
|

Post-abortion family planning use, method preference, and its determinant factors in Eastern Africa: a systematic review and meta-analysis

Abstract: Background Utilization of post-abortion family planning is very critical to reduce high levels of unintended pregnancy, which is the root cause of induced abortion. In Eastern Africa, it is estimated that as many as 95% of unintended pregnancies occurred among women who do not practice contraception at all. Therefore, this meta-analysis aimed to assess post-abortion family planning utilization and its determinant factors in Eastern Africa. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(51 reference statements)
7
4
1
1
Order By: Relevance
“…In this study, women who had a previous history of abortion were 89% more likely to utilize postabortion contraceptives compared to their counterparts. This is consistent with other studies done in East Africa and other parts of the country [ 22 , 30 , 34 ]. The possible explanation could be that the previous exposure to abortion might sensitize and influence the awareness of women towards postabortion contraceptive utilization.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, women who had a previous history of abortion were 89% more likely to utilize postabortion contraceptives compared to their counterparts. This is consistent with other studies done in East Africa and other parts of the country [ 22 , 30 , 34 ]. The possible explanation could be that the previous exposure to abortion might sensitize and influence the awareness of women towards postabortion contraceptive utilization.…”
Section: Discussionsupporting
confidence: 94%
“…Multigravida women were 8 times more likely to utilize postabortion contraceptives than primigravida. This finding was supported by the studies conducted in East Africa and other parts of Ethiopia [ 30 , 33 ]. This is due to the fact that women who had conceived frequently would choose to space birth compared to primigravida which might be related to socioeconomic or other related issues.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, the study by Erko et al revealed that married women were 6.7 times more likely to utilize post-abortion family planning than unmarried women [ 25 ]. It was thought that married women may be likely to be having sex more regularly than unmarried women, which may explain their high post-abortion family planning utilization [ 26 ]. With parity, the results revealed that 39% of women were nullipara.…”
Section: Presentation Of Findingsmentioning
confidence: 99%